The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1152/jn.00802.2014
|View full text |Cite
|
Sign up to set email alerts
|

A common stochastic accumulator with effector-dependent noise can explain eye-hand coordination

Abstract: The computational architecture that enables the flexible coupling between otherwise independent eye and hand effector systems is not understood. By using a drift diffusion framework, in which variability of the reaction time (RT) distribution scales with mean RT, we tested the ability of a common stochastic accumulator to explain eye-hand coordination. Using a combination of behavior, computational modeling and electromyography, we show how a single stochastic accumulator to threshold, followed by noisy effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…1), which is a modified version of a double-step paradigm with a countermanding signal incorporated in it. This data set was also used in two earlier published papers to test the common command hypothesis, which is the starting premise of the present work (Gopal et al 2015;Gopal and Murthy 2015). Visual cues (isoluminant colored squares), which subtended a visual angle of 1°, were used as targets in no-step trials (60%) and step trials (40%), which were randomly interleaved ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1), which is a modified version of a double-step paradigm with a countermanding signal incorporated in it. This data set was also used in two earlier published papers to test the common command hypothesis, which is the starting premise of the present work (Gopal et al 2015;Gopal and Murthy 2015). Visual cues (isoluminant colored squares), which subtended a visual angle of 1°, were used as targets in no-step trials (60%) and step trials (40%), which were randomly interleaved ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these movements were not natural reaching movements but involved the use of button presses and joysticks instead. However, in previous work we have shown that when eye-hand RT correlation is strong, combined eye and hand movements appear to engage a common motor command, which is qualitatively distinct from planning of eye and hand movements made in isolation (Gopal et al 2015;Gopal and Murthy 2015). Here we test whether effector-specific multiple control signals or a single control signal is recruited to control coordinated eye-hand movements.…”
mentioning
confidence: 86%
See 3 more Smart Citations